Food tolerance, nutritional status and health-related quality of life of patients with morbid obesity after bariatric surgery - Tsen, Poh Yue; Mohd Yusof, Barakatun Nisak; Nor Hanipah, Zubaidah; Gee, Tikfu (Elsevier, 2022)
Background and aims: Bariatric surgery has been proven to be the most effective weight loss treatment for patients with morbid obesity. However, the alteration in the anatomy of the gastrointestinal structure, food aversion, and non-compliance to recommended dietary advice after bariatric surgery may cause food intolerance, which may affect the nutritional status and health-related quality of life (HRQOL). This study aims to determine the effects of bariatric surgery on food tolerance, nutritional status, and HRQOL among patients with morbid obesity in Malaysia. Methods: This prospective observational study screened a total of 97 patients with morbid obesity. Data on socio-demographic characteristic, food tolerance, nutritional status and HRQOL were collected and assessed at baseline, one month and three months after bariatric surgery. Food tolerance was evaluated using a validated quality of alimentation questionnaire. The anthropometry measurements, including the body mass index (BMI) and percent excess weight loss (EWL), were evaluated, and the dietary intake was collected using a three-day food record. The HRQOL was assessed using the World Health Organization Quality of Life-BREF (WHOQOL-BREF) questionnaire. Results: This study recruited 90 patients with morbid obesity who underwent bariatric surgery with a response rate of 100%. There were 62 females (68.9%) and 28 male (31.1%) patients, with 50% of the patient age less than 40. The EWL one month and three months after surgery was 14.1% and 31.6%, respectively. There was a significant decrease in the total food tolerance score from 26.4 (SD = 0.8) at baseline to 17.7 (SD = 4.7) one month after bariatric surgery, but a gradual rise in the score to 21.7 (SD = 4.3) was observed three months after surgery. A similar pattern is seen in the dietary intake assessment where a significant reduction in the total energy from 1842 kcal (SD = 445) at baseline to 570 kcal (SD = 180) one month and an increase to 731 kcal (SD = 185) three months after bariatric surgery. The HRQOL of the study patients showed a statistically significantly increase in the domain of physical health (t = −7.253, p = < 0.001), psychological (t = −7.692, p < 0.001), social relationship (t = −5.767, p < 0.001) and environment (t = −4.208, p < 0.013) three months after bariatric surgery. Conclusion: The present study showed that bariatric surgery effectively reduces weight and improves overall HRQOL domains among patients with morbid obesity despite reduced food tolerance and energy intake after bariatric surgery. Future longitudinal studies or randomized controlled trial with a larger sample size is recommended to determine the cause and effect mechanism between food tolerance, weight loss, dietary intake, HRQOL and bariatric surgery in Malaysia. © 2022 European Society for Clinical Nutrition and Metabolism